Genomics of mucoepidermoid and adenoid cystic carcinomas. Issue 1 (8th February 2018) - Yan, Kenneth; Yesensky, Jessica; Hasina, Rifat; Agrawal, Nishant
Abstract : Objective: To report on the current state of the literature on the genetics of mucoepidermoid and adenoid cystic carcinomas of the salivary glands with a focus on genomic screens and recently discovered genetic translocations. Methods: A PubMed based literature review was performed to query for genetics related basic science and preclinical studies about mucoepidermoid and adenoid cystic carcinomas of the salivary glands. Results and conclusions: Genetic translocations between CRTC1 and MAML2 in mucoepidermoid carcinoma and between MYB and NFIB in adenoid cystic carcinoma have been recently discovered and have therapeutic implications. Key signaling pathways such as the EGFR pathway in mucoepidermoid carcinoma and the Notch pathway, chromatin regulation, and c‐kit mediated epithelial‐mesenchymal transitions in adenoid cystic carcinoma have recently been elucidated, pointing to possible therapeutic targets in both cancers.